PERHITUNGAN FAKTOR EMISI DI SISTEM JARINGAN KETENAGALISTRIKAN JAWA-MADURA-BALI - Irhan Febijanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The methodology of calculation for emission factor for grid connection is determined by IPCCC Intergovernmental Panel Climate Change). The methodology is revised periodically,and become comprehensive calculation. Mainly in developed countries, the emission factor is provided by government related institution yearly. Therefore the developers who need that value can get easily, and they can save a time and money in the developing Clean Development Mechanism Project. In Indonesia, until now there is no government institution or other related institutions that have an obligation to provide and calculate that number.PTPSE-BPPT has initiated to calculate the emission factor of grid system of Jawa-Madura-Bali using data between 2002 and 2006. The Approved Consolidated Methodology 0002 and Approved Methodology Simple I-D were used in the calculation. Based on the calculationresult, it was proved that the emission factor of JAMALI grid increased 18.2%, resulted to coal consumption increased. The value of this emission factor has been adopted by Directorate General Electricity and energy Utilization and recognized by Indonesian Designated National Authority, as a National Number of emission factor in JAMALI in 2008.Keywords : faktor emisi, emisi karbon, sistem JAMALI, pembangkit listrik,Clean Development Mechanism,